Using Google Classroom and Zoom Video Conference to Improve Formal Invitation Writing Skill - Innike Farastutie (ELLITE, 2022)
COVID-19 pandemic has presented challenges for all educational institutions in Indonesia. Learning process takes place online. The condition of students at senior high school which I studied during the covid 19 pandemic with online learning and its obstacles, affected the formal invitation writing skill scores of students who were still below the student learning achievement target which is 76%-85%. Therefore, it is important for teachers to create situations that will make it easier for students to write and reduce boredom. To overcome problems and barriers to online learning with the media of google classroom and zoom meetings during the covid 19 pandemic, researchers need to provide a process and product-oriented learning model that is Project Based Learning; a student-cantered learning model and it was considered the most suitable for indirect learning during the covid 19 pandemic. This research method uses Class Action Research. The reason for using it is to improve the learning process problems that arise encountered in learning. The results showed that students’ learning achievement has improved from cycle I cycle I (68.42%) to cycle II (78.95%) and the average score achieved increased from 69.47 in cycle 1 becomes 77, 37 in cycle 2. And the output data from the paired sample t-test is known to have a significance value (2-tailed) 0.000 < 0.05, so it can be concluded that there is a significant difference in learning outcomes from cycle 1 to cycle 2.